If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 12 = -28 + -6x Reorder the terms: 12 + 2x = -28 + -6x Solving 12 + 2x = -28 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 12 + 2x + 6x = -28 + -6x + 6x Combine like terms: 2x + 6x = 8x 12 + 8x = -28 + -6x + 6x Combine like terms: -6x + 6x = 0 12 + 8x = -28 + 0 12 + 8x = -28 Add '-12' to each side of the equation. 12 + -12 + 8x = -28 + -12 Combine like terms: 12 + -12 = 0 0 + 8x = -28 + -12 8x = -28 + -12 Combine like terms: -28 + -12 = -40 8x = -40 Divide each side by '8'. x = -5 Simplifying x = -5
| x=mk+mn | | (4x+20)+(3x+40)=180 | | solvemk+mn=xform | | -3-2(5-2x)=(2x-5) | | 3+5x=-1+x | | 6x+8=-40-2 | | (-a)-b=(-b)-a | | 7=z+9 | | 9z+1=46 | | 2ln(3-x)=1 | | -a-b=-b-a | | 11x+7x+90=x+x | | b+2a+c= | | x-2/3-x+1/4=x | | 8w-1=31 | | -3(x-1)=x-5 | | x+75=x+115 | | 7(n-5)-(8n-1)=-2n | | -6x+y=16 | | 10+10t-5t^2=0 | | 6b+10=46 | | 4(x+8)=-60 | | 18x+90=2x | | 0.5(x+4)=197 | | x+88=108+x | | 4x+60+x=180 | | 14x^2+70x+25=48 | | 2w+100=4w | | 3a+2b=5ab | | 6(c-9)=-24 | | 2[7-7(1-x)]+4x=-16+3[6(x+1)-3x] | | 7f=42 |